Comparison of Efficacy Between Endoscopic Cyclophotocoagulation and Alternative Surgeries in Refractory Glaucoma: A Meta-analysis. Issue 39 (September 2015) - Yang, Yangfan; Zhong, Jing; Dun, Zhongjun; Liu, Xiao-an; Yu, Minbin
Abstract : Abstract: Refractory glaucoma refers to uncontrolled intraocular pressure (IOP) despite anti-glaucoma medication and surgical treatment, which remains a challenge to be treated. The objective of this study is to evaluate and statistically compare the clinical efficacy between endoscopic cyclophotocoagulation (ECP) and alternative surgical techniques in the treatment of refractory glaucoma in this article, as a meta-analysis. Data sources are China Biomedical Database (Sinomed, online version), China National Knowledge Infrastructure (CNKI), Cqvip, Wanfang database, and PubMed. The randomized controlled trial (RCT) and case–control study literatures evaluating the clinical efficacy between ECP and other surgical techniques were searched electronically from public databases. The methodology quality of the retrieved articles was evaluated according to the RCT or case–control study criteria. The success rate of treatment, intraocular pressure (IOP) and visual acuity were statistically compared. RevMan 5.3 software was used for the meta-analysis. In total, 6 relevant control studies were selected in this study with a total sampling of 429 cases (429 eyes), including 204 eyes in the ECP group and 225 in the non-ECP group. Meta-analysis demonstrated that the clinical efficacy did not significantly differ between 2 groups ( P > 0.05). Postoperative IOP was dramatically reduced in both groups. However, it was difficult to evaluate the combined influence of ECP and non-ECP therapies upon IOP reduction. In conclusion, ECP and non-ECP treatment yielded almost equivalent clinical efficacy in treating refractory glaucoma. The IOP-lowering degree, safety, and incidence of complications remain to be further elucidated by RCTs with a larger sample size.